Detection of Human Papillomavirus in Korean Breast Cancer Patients by Real-Time Polymerase Chain Reaction and Meta-Analysis of Human Papillomavirus and Breast Cancer - Jinhyuk Choi; Chungyeul Kim; Hye Seung Lee; Yoo Jin Choi; Ha Yeon Kim; Jinhwan Lee; Hyeyoon Chang; Aeree Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background Human papillomavirus (HPV) is a well-established oncogenic virus of cervical, anogenital, and oropharyngeal cancer. Various subtypes of HPV have been detected in 0% to 60% of breast cancers. The roles of HPV in the carcinogenesis of breast cancer remain controversial. This study was performed to determine the prevalence of HPV-positive breast cancer in Korean patients and to evaluate the possibility of carcinogenic effect of HPV on breast. Methods Meta-analysis was performed in 22 case-control studies for HPV infection in breast cancer. A total of 123 breast cancers, nine intraductal papillomas and 13 nipple tissues of patients with proven cervical HPV infection were tested by real-time polymerase chain reaction to detect 28 subtypes of HPV. Breast cancers were composed of 106 formalin-fixed and paraffin embedded (FFPE) breast cancer samples and 17 touch imprint cytology samples of breast cancers. Results The overall odds ratio between breast cancer and HPV infection was 5.43 (95% confidence interval, 3.24 to 9.12) with I2 = 34.5% in meta-analysis of published studies with case-control setting and it was statistically significant. HPV was detected in 22 cases of breast cancers (17.9%) and two cases of intaductal papillomas (22.2%). However, these cases had weak positivity. Conclusions These results failed to serve as significant evidence to support the relationship between HPV and breast cancer. Further study with larger epidemiologic population is merited to determine the relationship between HPV and breast cancer.